Enhancing Public Service Excellence through Transformational Leadership in Service Management - Aji Wahyudin; Fadhil Akbar; Rohmad Rohmad; M Hanif Satria Budi (Business and Applied Management Journal, 2024)
This study aims to explore the impact of transformational leadership on improving education in Islamic primary schools. The study was motivated by the increasing need for effective leadership in educational institutions to adapt to the demands of an ever-evolving society and foster a culture of excellence. Transformational leadership, known for its ability to inspire and empower subordinates, has been proposed as a key factor in driving positive change in educational environments. A qualitative case study approach was used, using participant observation, in-depth interviews, and document analysis to collect data. The findings of the study indicate that transformational leadership in Islamic primary schools has significantly increased teacher motivation, collaboration, and commitment to school development. Teachers reported feeling more involved in the decision-making process, leading to improved teaching practices and overall school performance. The village head’s leadership, characterized by openness, empathy, and teacher empowerment, created an environment conducive to continued growth. This study is expected to contribute to the understanding of how transformational leadership can positively impact educational institutions, providing valuable insights for other schools seeking to implement change and improve the quality of their services.